AUDIT SISTEM INFORMASI AKADEMIK UNIVERSITAS PRIMAGRAHA MENGGUNAKAN COBIT 5 FRAMEWORK - Adith Aulia Rahman (Amal Insani Foundation, 2022)
An academic information system is an application created to be an academic governance information system such as lecturer and student data, online KRS system, academic schedules, etc. Poor governance of academic information systems can affect the credibility of the institution itself due to reduced trust in the use of these applications by stakeholders. By carrying out regular monitoring and evaluation, it is hoped that it can improve if there needs to be better governance of academic information system applications. In this paper, the stage is to conduct a system audit of academic information system applications using the COBIT framework. The steps taken in the audit process are: 1. Planning, 2. Fieldwork, 3. Reporting 4. Follow-up. By using the calculation results from each information technology process contained in the Delivery and Support (DS) and Monitor, Evaluate, and Asses (MEA) domains, the overall information technology can reach the desired level.